Social disparities in the frequency and severity of triple-negative breast cancer at diagnosis in a university hospital in Paris, France: confronting race and ethnic blindness - Pierre Chauvin; Thomas Huet; Joseph Gligorov; Carolyn Sargent (PLoS ONE, 2026)
Triple-negative breast cancer (TNBC), an aggressive subtype with poor prognosis, is of higher frequency in African American women and women of Sub-Saharan African origin. In France, legal constraints on obtaining health data on race, ethnicity, or nationality in cancer registries and medical records make it difficult to estimate the frequency of TNBC according to women’s origins. These constraints result from a historical “universalist” approach to French citizenship which prohibits the routine collection of ethnoracial data. An anonymous, statistical survey we conducted from a single-hospital case series of 780 women with breast cancer followed in a university hospital in Paris showed that TNBCs were at least 3 times more common in patients born in Sub-Saharan Africa than in patients born in France. The former consulted at a more advanced stage of the disease than the latter. The results of an ethnographic study of African women in the Paris region with breast cancer, conducted for several years, highlighted some explanatory factors: low breast cancer awareness, perceived causes distinct from biomedical etiology, the weight of shame and secrecy, prior recourse to local healing, difficulties in communicating with health professionals and navigating the healthcare system. Although considered a public health priority, TNBCs are an emblematic example of the limits produced by French race and ethnicity blindness in public health, epidemiology, prevention and health care.